Contribuições das múltiplas linguagens nos processos de ensino e de aprendizagem da língua escrita na pré-escola - Capinos, Graciele Berno (My University, 2023)
This research explores the utilization of the Reggio Emilia approach regarding multiple languages to aid the processes of teaching and learning written language, emphasizing the plurality of languages instead of traditional literacy methods. According to Malaguzzi (1999, 2016, 2017); Edwards, Gandini, and Forman (1999, 2016); Vechi (2017); Rinaldi (1999, 2014, 2021), and Hoyuelos (2020a, 2020b, 2021), the discursive interactions of children in multiple languages allow them to navigate both oral and written modalities. The aim is to broaden the conception of methodologies contributing to written language learning in preschool. The goal is to investigate how the Reggio Emilia approach, interpreted here as "multiple languages," contributes to developing written language in Early Childhood Education, specifically preschool. The theoretical framework draws on linguistics contributions to literacy (Soares, 2016, 2020), a sociocultural perspective on literacy with a constructivist basis by Ferreiro and Teberosky (1999), and constructivist-interactionist theories of Vigotski (1998a, 1998b, 1998c, 2009, 2014). It also aligns with interactive perspectives, particularly the works of Smolka (1993, 2017), Bakhtin (1997, 2006), Mortatti (2000a, 2000b, 2007, 2019a), Goulart (2014, 2016, 2020), Geraldi (2011), Marcuschi (2007), and Soares (2009a, 2009b, 2015, 2020). This study adopts a bibliographic and document analysis approach as per Cellard (2008) and Lüdke e André (1986), focusing on the analysis of written language teaching and the presence of multiple languages in the textbook. After exploring the literature, it was observed that the provision of textbooks for preschool children limited pedagogical practices to literacy and numeracy content, as proposed in the National Literacy Policy (Brazil, 2019), diverging from the proposals of the Common National Common Curricular Base for Early Childhood Education (Brazil, 2017). The textbooks did not adequately incorporate multiple languages. However, written language instruction in textbooks is mainly tied to traditional literacy methods such as alphabet memorization, word copying, and letter sounds. In conclusion, multiple languages could be present in preschool to facilitate learning written language and mathematics, but also other languages relevant to developing discursive practices involving interactions between subjects and language, valuing text, oral communication, writing, and life. [resumo fornecido pelo autor]
Esta pesquisa compreende a utilização da abordagem Reggio Emilia, quanto às múltiplas linguagens, capaz de auxiliar os processos de ensino e aprendizagem da língua escrita, no que tange à pluralidade de linguagens, no lugar dos métodos tradicionais de alfabetização. As interações discursivas das crianças, nas múltiplas linguagens, de acordo com Malaguzzi (1999, 2016, 2017); Edwards; Gandini; Forman (1999, 2016); Vechi (2017); Rinaldi (1999, 2014, 2021) e Hoyuelos (2020a, 2020b, 2021), permitem que elas transitem pelas duas modalidades da linguagem, oral e escrita, de modo que as múltiplas linguagens ampliem a concepção da utilização de metodologias para contribuir na aprendizagem da língua escrita na pré-escola. O objetivo geral desta pesquisa é investigar como a abordagem Reggio Emilia, assumida aqui como "múltiplas linguagens", contribui para o desenvolvimento da língua escrita na Educação Infantil, pré-escola. O referencial teórico adotado tem como base as contribuições da linguística, acerca da alfabetização, conforme ressalta Soares (2016, 2020); do letramento na perspectiva sociocultural, de base teórica construtivista, de Ferreiro e Teberosky (1999), de base teórica construtivista interacionista de Vigotski (1998a, 1998b, 1998c, 2009, 2014) e interativa, dedicando-se, especialmente, às obras de Smolka (1993, 2017); Bakhtin (1997, 2006); Mortatti (2000a, 2000b, 2007, 2019a); Goulart (2014, 2016, 2020); Geraldi (2011); Marcuschi (2007) e Soares (2009a, 2009b, 2015, 2020). Nesse cenário, este estudo se configura com uma abordagem bibliográfica, de análise documental, segundo Cellard (2008) e Lüdke e André (1986), voltado à análise do ensino da língua escrita e da presença das múltiplas linguagens no livro didático. Após a exploração das postulações dos autores que compõe a literatura adotada, com base na análise do livro didático realizada nesta pesquisa, compreendeu-se que a oferta do livro didático para crianças da Educação Infantil, pré-escola, limitaram as práticas pedagógicas e estão associadas às aprendizagens de conteúdos de literacia e numeracia, como propostas na Política Nacional de Alfabetização (Brasil, 2019), distanciando-se das proposições da Base Nacional Comum Curricular na Educação Infantil (Brasil, 2017), não contemplando as múltiplas linguagens. No entanto, o ensino da língua escrita no livro didático está atrelado, basicamente, aos métodos tradicionais de alfabetização, como a memorização do alfabeto, cópia de palavras e sons das letras. Infere-se, portanto, que as múltiplas linguagens poderiam estar presentes na pré-escola, a fim de propiciar uma aprendizagem não somente da língua escrita e da matemática, mas de outras linguagens, que são relevantes para o desenvolvimento das práticas discursivas de interação em construções entre sujeito e linguagem, que valorizam o texto, a oralidade, a escrita e a vida. [resumo fornecido pelo autor]
Keywords: Educação de crianças; Alfabetização; Letramento; Education of children; Literacy